1997
DOI: 10.1179/oeh.1997.3.3.190
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Course of Musculoskeletal Symptoms and Clinical Findings in Upper Extremities of Female Milkers

Abstract: To explore milkers' state of health with regard to symptoms in the wrists and hands, a study of 80 female milkers was carried out 12 months after a Nordic questionnaire study of these subjects. Of these 80, 41 had reported pain and discomfort in the wrists and hands at the time of the questionnaire study, whereas the remaining 39 had had no such symptoms. To determine the sensitivity and specificity of the Nordic questionnaire, the follow-up study included examination by an unbiased clinician. The occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
2
14
1
2
Order By: Relevance
“…This is in contrast to several other studies that reported higher prevalences for questionnaires compared to physical examinations (Zetterberg et al 1997;Nordander et al 1999;Toomingas et al 1995;Bjorksten et al 1999;Salerno et al 2000). Other studies report sensitivities of 52-60 % (Stål et al 1997), 97 % for the neck and shoulders (Bjorksten et al 1999) and 50-89 % (Akesson et al 1999), and specificities of 86-98, 41 and 55-89 %, respectively. Although not reported in the results section, these values are comparable to values found in the present study with sensitivity ranging 33-70 % and specificity ranging 75-94 %.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskcontrasting
confidence: 58%
See 1 more Smart Citation
“…This is in contrast to several other studies that reported higher prevalences for questionnaires compared to physical examinations (Zetterberg et al 1997;Nordander et al 1999;Toomingas et al 1995;Bjorksten et al 1999;Salerno et al 2000). Other studies report sensitivities of 52-60 % (Stål et al 1997), 97 % for the neck and shoulders (Bjorksten et al 1999) and 50-89 % (Akesson et al 1999), and specificities of 86-98, 41 and 55-89 %, respectively. Although not reported in the results section, these values are comparable to values found in the present study with sensitivity ranging 33-70 % and specificity ranging 75-94 %.…”
Section: Validity Of Using Questionnaires For Assessment Of Musculoskcontrasting
confidence: 58%
“…The internal consistency, reliability and concurrent validity of questions on work-related exposure were found to be acceptable (Speklé et al 2009). The symptom-related questions of the RSI QuickScan still need to be validated by comparing outcomes with physical examinations by occupational physicians (Ohlsson et al 1994;Zetterberg et al 1997;Nordander et al 1999;Toomingas et al 1995;Bjorksten et al 1999;Salerno et al 2000;Stål et al 1997;Akesson et al 1999;Kaergaard et al 2000;Juul-Kristensen et al 2006), usually recognized as more objective than questionnaires (Perreault et al 2008). Therefore, the main objective of the present study was to determine the concurrent validity of the symptom-related questions of the RSI QuickScan by assessing the agreement between the results of these self-administered questions and the physical examination by occupational physicians on the presence of arm, shoulder or neck symptoms in computer workers with and without arm, shoulder or neck symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Over a 31-month period in a meat-processing factory in Finland, of 337 workers in strenuous manual jobs, only one stopped working because of an upper-limb illness, and job transfers were rare (27). In some contexts selection bias seems to be minimal (20,23). Selection effects may be greater in the general population than in some prospective epidemiologic studies, since a prospective study is not feasible in a firm with a high level of turnover.…”
Section: Discussionmentioning
confidence: 89%
“…The main objectives have been to estimate the incidence and improve knowledge of the frequency and natural course of specific disorders or to study the effects of changes in exposure or occupation (20)(21)(22)(23)(24)(25)(26)(27). Findings from these studies are not always comparable; for example, the term "incidence" is used with several meanings, including the rate of absenteeism episodes (27).…”
mentioning
confidence: 99%
“…SE = 0.83 [0.79, 0.87]; SP = 0.81 [0.79, 0.83]Sensitivity moderate, specificity moderateRestrictive (pain scale rating (PS) and symptoms during examination)RestrictiveNMQ, GS > 0: k  = 0.44 (95% CI 0.40–0.48)NMQ, GS > 0: SE = 0.82 [0.78, 0.86]; SP = 0.82 [0.81, 0.84]NMQ, GS ≥ 2: k  = 0.45 (95% CI 0.41–0.49) Agreement moderateNMQ, GS ≥ 2; SE = 1.00 [0.99, 1.00]; SP = 0.51 [0.49, 0.53]Sensitivity moderate to high, specificity low to moderate3Juul-Kristensen et al (2006)MSD Upper ExtremitiesSymptomsSE = 0.86 [0.68, 0.96]; SP = 0.77 [0.66, 0.86]Sensitivity high, specificity moderate4Ohlsson et al (1994)MSD Upper extremitiesSymptomsAll regions combined, related to diagnosesHigher sensitivity related to diagnoses, higher specificity related to clinical findingsSE = 0.83 [0.72, 0.90]; SP = 0.64 [0.54, 0.74]All regions combined, related to clinical findingsSE = 0.66 [0.57, 0.74]; SP = 0.92 [0.74, 0.99]Sensitivity moderate to high, specificity low to moderate5Perreault et al (2008)MSD Upper ExtremitiesSymptomsSE = 0.66 [0.56, 0.75]; SP = 0.79 [0.69, 0.87]Agreement self-report to physicians assessment 72%; k  = 0.44 (95% CI 0.31–0.56): moderateSensitivity low, specificity moderateVariable agreement when using different case definitions (symptoms, limitations ADL, limitations work, limitations leisure): k  = 0.19–0.546Stål et al (1997)MSD Upper ExtremitiesSymptomsAll regions combined: SE = 0.57 [0.42, 0.71]; SP = 0.72 [0.53, 0.87] sensitivity low; specificity moderateHigher sensitivity related to diagnoses, higher specificity related to clinical findingsFor separate regions variable sensitivity and specificity for either clinical findin...…”
Section: Resultsmentioning
confidence: 99%